2014
DOI: 10.1080/09168451.2014.930318
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Typhae total flavone improves insulin resistance in high-fat diet and low-dose streptozotocin-induced type 2 diabetic rats

Abstract: (2014) PollenTyphae total flavone improves insulin resistance in high-fat diet and lowdose streptozotocin-induced type 2 diabetic rats, Bioscience, Biotechnology, and Biochemistry,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Moreover, lipid accumulation, lipid peroxidation, and systemic inflammation in T2DM patients, at least partially, help to reflect IR (Mirmiran et al, 2014;Feng et al, 2016). To date, several agents, such as fresh pomegranate juice (Banihani et al, 2014), sodium salicylate (Jiang et al, 2015), Pollen Typhae total flavone (Feng et al, 2014), gallic acid (Gandhi et al, 2014), and a-mangostin (Mekseepralard et al, 2015), have been reported to combate IR in T2DM patients or T2DM rats. Interestingly, these above-mentioned agents are mostly natural ingredients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, lipid accumulation, lipid peroxidation, and systemic inflammation in T2DM patients, at least partially, help to reflect IR (Mirmiran et al, 2014;Feng et al, 2016). To date, several agents, such as fresh pomegranate juice (Banihani et al, 2014), sodium salicylate (Jiang et al, 2015), Pollen Typhae total flavone (Feng et al, 2014), gallic acid (Gandhi et al, 2014), and a-mangostin (Mekseepralard et al, 2015), have been reported to combate IR in T2DM patients or T2DM rats. Interestingly, these above-mentioned agents are mostly natural ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…T2DM patients exhibit impaired glucose tolerance, hyperglycemia, hyperinsulinemia, dyslipidemia, and finally insulin deficiency (Daneshgari et al, 2017). T2DM is due to insulin resistance (IR), characterized by a defect of the peripheral tissues, including liver, adipose tissues, and skeletal muscles, in response to insulin (Feng et al, 2014). IR is the core mechanism of T2DM and thus has become the main target of T2DM treatment at this stage (Jiang et al, 2015;Garabadu and Krishnamurthy, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissues, the key insulin targeted tissues, play an important role in PTF improves insulin resistance in type 2 diabetic rats induced by high-fat diet and low-dose streptozotocin (Feng et al 2014). Additionally, PTF can not affect PI3K activity in C2C12 myotubes (Feng et al 2012a), a critical node in PI3K pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Pollen Typhae has been widely used to treat type 2 diabetes and other diseases characterized by insulin resistance such as metabolic syndrome and non-alcohol fatty liver disease in China. We have ever reported that Pollen Typhae total flavone (PTF), the extract from Pollen Typhae which mainly contains typhaneoside and other constituents (Feng et al 2012a), ameliorates insulin resistance in type 2 diabetic rats (Feng et al 2014), but the potential mechanisms remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Later, anti-inflammatory activity and antioxidant potential of Pollen Typhae Angustifoliae were also reported [15, 23]. Recently, Pollen Typhae Angustifolia was reported to improve insulin resistance in the high-fat diet and low-dose streptozotocin-induced type 2 diabetic rats [24]. In the present study, we clearly show that Pollen Typhae Angustifoliae alcohol extract could increase SR-BI promotor activity, mRNA, and protein expression in LO-2 cell line, indicating that Pollen Typhae Angustifolia is an effective component in Tiaozhi granule, which may play an important role in the treatment of HLP, therefore, processing antiatherosclerotic effect.…”
Section: Discussionmentioning
confidence: 99%